2020
DOI: 10.1371/journal.pgen.1008620
|View full text |Cite
|
Sign up to set email alerts
|

Histone H4 dosage modulates DNA damage response in the pathogenic yeast Candida glabrata via homologous recombination pathway

Abstract: Candida glabrata, a nosocomial fungal bloodstream pathogen, causes significant morbidity and mortality in hospitals worldwide. The ability to replicate in macrophages and survive a high level of oxidative stress contributes to its virulence in the mammalian host. However, the role of DNA repair and recombination mechanisms in its pathobiology is still being discovered. Here, we have characterized the response of C. glabrata to the methyl methanesulfonate (MMS)-induced DNA damage. We found that the MMS exposure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(24 citation statements)
references
References 58 publications
3
21
0
Order By: Relevance
“…For example, Candida glabrata is not only the second most common cause of invasive candidiasis of skin, mucosa and even viscera but also accounts for up to 30% of Candida bloodstream infections. 29 Candida parapsilosis is the second or third most frequently isolated Candida species from patients with invasive candidiasis. 27 Cladosporium species were reported to cause various super cial and invasive fungal infections, such as brain abscess and keratitis.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Candida glabrata is not only the second most common cause of invasive candidiasis of skin, mucosa and even viscera but also accounts for up to 30% of Candida bloodstream infections. 29 Candida parapsilosis is the second or third most frequently isolated Candida species from patients with invasive candidiasis. 27 Cladosporium species were reported to cause various super cial and invasive fungal infections, such as brain abscess and keratitis.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, MMS exposure was found to cause significant reduction in mRNA and protein amounts of both H3 and H4 histones in the pathogenic yeast C. glabrata , with low H4 gene dosage also giving rise to MMS resistance (Kumar et al 2020 ). In this study, we had shown a requirement for HR in the repair of MMS-induced DNA damage, and low H4 levels resulting in increased HR efficiency, faster repair of damaged DNA and MMS resistance (Kumar et al 2020 ). However, this MMS resistance was specific to the loss of two H4-encoding genes, probably due to the H4 amount produced by the remaining H4 ORF (Kumar et al 2020 ).…”
Section: Histones and Dna Damagementioning
confidence: 99%
“…However, this MMS resistance was specific to the loss of two H4-encoding genes, probably due to the H4 amount produced by the remaining H4 ORF (Kumar et al 2020 ). C. glabrata contains three histone H4 genes, CgHHF1, 2 and 3 , with CgHHF1 and 2 genes exhibiting synteny with their S. cerevisiae counterparts (Kumar et al 2020 ). Of these, while CgHHF1 and 2 gene loss rendered C. glabrata cells resistant to MMS, deletion of CgHHF2 and 3 genes made cells sensitive to MMS (Kumar et al 2020 ), indicating that the deletion of two H4 genes can have opposite biological consequences.…”
Section: Histones and Dna Damagementioning
confidence: 99%
See 2 more Smart Citations